Leveraging Clinical Decision Support in Dental Settings to Bridge HIV Testing Gaps and Contribute to Ending the Epidemic - Sharon C. Perelman; Tunaidi Ansari; Michael T. Yin; Peter G. Gordon; Nadia Nguyen; Vicky Evangelidis-Sakellson; Carol Kunzel; Kathrine Meyers; Delivette Castor; Ariel Blanchard; David A. Albert (ACI Open)
Background Columbia University Irving Medical Center (CUIMC) in New York City, in collaboration with the Division of Infectious Diseases and the Dental School, is addressing a critical gap in HIV testing to support the strategy to End the HIV Epidemic (EHE). This strategy emphasizes increasing testing rates and providing patients with information about pre-exposure prophylaxis (PrEP).